Estimation of a possibility of application fuzzy logic controller an air vessel in conditions of the special situation - Казак, В. Н.; Шевчук, Д. О. (Problems of Informatization and Control, 2004)
In the article is considered possibility of application of the fuzzy logic controller for development of control action in conditions of the special situation. The main principles are considered and the features of management on basis of the theory of fuzzy sets are revealed. The block diagram of a control system with the fuzzy logic controller is given. The problems are determined which necessary to decide for realization of the fuzzy logic controller